Combining implicit and explicit intervention approaches to target grammar in young children with Developmental Language Disorder - Calder, S.; Claessen, M.; Leitão, Suze (Sage Publications, 2018)
Children with Developmental Language Disorder are likely to experience difficulties with morphosyntax, especially regular past tense marking. Few studies have evaluated the effectiveness of intervention to improve morphosyntax in young school-aged children with DLD. This study investigated the efficacy of combined explicit and implicit intervention techniques delivered by a speech pathologist to improve receptive and expressive grammar, including the use of past tense morphosyntax, using a multiple baseline single case experimental design. Participants were aged six to seven years and received two 1:1 45 minute sessions per week for five weeks (total 7.5 hours) using Shape Coding intervention techniques combined with implicit approaches. Two of the three participants made statistically significant gains on standardized tests of general receptive and expressive grammar. Two of the three children made statistically significant improvement on measures of expressive morphosyntax, with one participant continuing to improve five weeks post treatment. Findings suggest that this approach was efficacious. These findings warrant further investigation using larger group comparison research studies.